PENGARUH PEMBELAJARAN PKn BERBASIS PROJECT CITIZEN TERHADAP HASIL BELAJAR SISWA SMA KELAS XI IPS SMA N 1 KOTA JAYAPURA - Emanuel Goo; Ode Jamal (FKIP Universitas Cenderawasih, 2025)
Abstrack: This study aims to analyze the effect of Project Citizen-based Civic Education (PKn) learning on the learning outcomes of eleventh-grade social studies (IPS) students at SMA N 1 Kota Jayapura. Low academic achievement is reflected in school evaluations that remain below the minimum mastery criteria. The research approach employed was quantitative with a quasi-experimental design, specifically utilizing a Nonequivalent Control Group Posttest-Only Design. The research subjects involved 44 students divided into two paired groups: 22 students in the experimental group undergoing the Project Citizen syntax treatment and 22 students in the control group using conventional methods. Data were collected through active participation observations and objective learning outcome tests following a six-week intervention. The results of descriptive and inferential statistical analyses using the Independent Sample t-Test indicated a significant improvement in the experimental group, which achieved a post-test mean score of 75.45 (p < 0.05). This research offers theoretical and practical contributions to innovative and contextual Civic Education curricula in Papua. Keywords: Project Citizen-Based Civics Learning, Learning Outcomes. Abstrak: Studi ini bertujuan menganalisis pengaruh pembelajaran Pendidikan Kewarganegaraan (PKn) berbasis Project Citizen terhadap hasil belajar siswa kelas XI IPS di SMA N 1 Kota Jayapura. Rendahnya capaian akademis tecermin dari evaluasi sekolah yang masih berada di bawah kriteria kelulusan minimal. Pendekatan penelitian menggunakan kuantitatif dengan desain eksperimen semu berbentuk Nonequivalent Control Group Posttest-Only Design. Subjek riset melibatkan 44 siswa yang terbagi secara berpasangan ke dalam kelompok eksperimen (22 siswa) dengan perlakuan sintaks Project Citizen dan kelompok kontrol (22 siswa) menggunakan metode konvensional. Data dikumpulkan melalui observasi partisipasi aktif dan instrumen tes hasil belajar objektif setelah intervensi selama enam minggu. Hasil statistik deskriptif dan inferensial menggunakan Independent Sample t-Test menunjukkan adanya peningkatan capaian yang signifikan pada kelompok eksperimen dengan perolehan rerata nilai akhir sebesar 75,45 (p < 0,05). Riset ini memberikan kontribusi teoretis serta praktis dalam inovasi kurikulum PKn kontekstual di Papua. Kata kunci: Pembelajaran PKn Berbaasis Project Citizen, Hasil Belajar.